A New Mens Rea for Rape: More Convictions and Less Punishment - Hong, Kari E. (2018)
There is no doubt that the law of rape is in need of reform. Compared to other crimes, reported rapes are convicted at 1/3 the rate of robberies and 1/6 the rate of assaults. Because knowing the identity of an assailant should lead to more, not fewer, convictions, this low conviction rate then is surprising given that acquaintance rapes—where the attacker is known to the victim—account for 80% of all rapes. Criminal law serves a vital purpose when it can clearly define criminal conduct and separate it from lawful activity. To effectively draw this line, criminal laws must evolve with social norms and capture the underlying social harm of the conduct. For instance, manslaughter was reformed to criminalize deaths arising from horseless carriages and theft statutes were updated to capture the harm arising from hacking into a computer. But rape law has been stunted, with definitions limited to the crime’s actus reus of either force or non-consent. Unlike homicide and theft offenses, rape law has not benefitted from having liability arise from more sophisticated mental states. If a person drives a car in a crowd and kills another, that person had neither knowledge nor purpose to kill. The driver nonetheless would be liable for murder under the mens rea of malice—the capacious mental state capturing acts accompanied by a heightened recklessness, extreme indifference, or contempt over whether her actions presented a possibility of death. This Article proposes a crime of rape defined by the mens rea of malice. Rape by malice reflects the contemporary understandings of what is the social wrong in having unwanted sex—it is a defendant acting with intent to have sex without consent, reckless disregard of risk of having sex without consent, or extreme indifference over whether he is having sex with the consent of his partner. Although rape by malice will lead to more convictions, punishing more rapists under the current criminal justice system should not be welcomed. A second point of this Article is to recognize the reality of rape laws’ connection to mass incarceration. Where statistics are available, current rape convictions are met with lengthy, and I argue, excessive prison terms that range from eight to thirty years. Potential sentences are up to 100 years. If the United States is serious about stopping mass incarceration, sentence reform must extend to more than drug crimes. This Article proposes a five-year prison term for rape offenses that do not involve children or weapons. It is mistake to assume that a light sentence fails to communicate that the crime is heinous and the offender is depraved. Rather, a maximum five-year sentence adequately punishes the offender, prevents overpunishment, leads to more convictions, reduces recidivism, and comports with international sentencing practices